Non-economic Emigration Factors that Might be Pushing Citizens Out of Lithuania - Thomas Andrew Bryer; Rimantas Rauleckas; Vishnu Muraleedharan; Eglė Butkevičienė; Jolanta Vaičiūnienė; Eglė Vaidelytė; Ramunė Miežanskienė (Public Policy and Administration, 2020)
Based on a systematic and comprehensive review of literature on emigration, we identify potential non-economic push factors that might drive Lithuanian citizens to emigrate. Based on a random sample nationwide survey conducted in spring 2019 with Lithuanian citizens living in Lithuania, two categories have emerged as most critical non-economic drivers to lead to higher intention to emigrate: quality of working life and confidence in the future. Further research can add necessary nuance to understanding these factors while also experimenting with possible policy and project interventions that can reduce intent to emigrate and/or encourage return migration. This research is implemented under the project "The importance of non-economic factors to the emigration of the Lithuanian population", funded by the Research Council of Lithuania under the Programme "Improvement of researchers' qualification by implementing world-class R&D projects" (Agreement No. 09.3.3-LMT-K-712-01-170).